Principal Leadership in Building Quality Schools: A Case Study in Elementary School - Jasiah Jasiah; David Budi Irawan; Adrianus Dedy; Aldora Pratama; Reza Syahbandi (STKIP Yapis Dompu, 2023)
SD IT An Nafirah Palembang has educational method was influenced by the leadership of the principal. Leadership from the principal placed more emphasis on developing students' character than on their grades. This study aimed to describe the leadership style used and the function of principals as leaders in the development of high-quality schools. Research of this kind was qualitative. Phenomenology was the research methodology employed. In addition to using secondary data—documents received from the school—research also employed primary data—interviews and observations. An interactive model analysis with source triangulation and procedures was employed to analyze the data. The study's findings were as follows: First, the leadership style used by the principals was democratic-monarchic. This was based on the framework that was used to determine policies and carry out cooperative decision-making processes. Second, the principal's function encompassed a variety of responsibilities that were fulfilled, including those of an educator, manager, administrator, supervisor, leader, innovator, and highly effective motivator. The principal could serve as an illustration of how to perform their tasks. Therefore, it is important to correctly monitor and evaluate the leader's personality.